2013
DOI: 10.1007/s11136-013-0612-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative aspects of well-being as correlates of breast reconstruction decision

Abstract: The results suggest that positive rather than negative aspects of well-being, after control for sociodemographic variables, may be significant correlates of breast reconstruction decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In this study, no definite predictive strength of these two variables for BR was confirmed. Similar results were observed in a recent cross-sectional cohort study of 216 Polish women by Zycinska et al [ 50 ] They concluded that depression and anxiety, as negative aspects of well-being following mastectomy, had less direct effects on the patients’ intention to undergo BR.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, no definite predictive strength of these two variables for BR was confirmed. Similar results were observed in a recent cross-sectional cohort study of 216 Polish women by Zycinska et al [ 50 ] They concluded that depression and anxiety, as negative aspects of well-being following mastectomy, had less direct effects on the patients’ intention to undergo BR.…”
Section: Discussionsupporting
confidence: 89%
“…However, a sense of ownership can lead to territorial behaviors (Brown et al, 2014) that threaten to decrease wellbeing. Considering that PO can lead to both promotion and prevention outcomes (Higgins, 1998), it suggests a conceptual alignment with work on value co-creation and value co-destruction (Echeverri and Sk al en, 2011;Pl e and Chumpitaz C aceres, 2010) as well as wellbeing improvement (positive wellbeing) and wellbeing deterioration (negative wellbeing) (Zycinska et al, 2014). This reasoning is the starting point for this paper's investigation and in line with work claiming that feelings of PO stimulate behaviors that contribute to the target of ownership's wellbeing (Van Dyne and Pierce, 2004).…”
Section: Theoretical Framework Psychological Ownership (Po)mentioning
confidence: 99%
“…Human actors can contribute in various ways to improve their wellbeing (McColl-Kennedy et al, 2012), and ideally should adopt an active stance (Caru and Cova, 2015;Prahalad and Ramaswamy, 2004) to "take ownership of [their] health" (Saint Thomas, 2016). However, while individual actors' efforts are required to improve their own wellbeing (Sweeney et al, 2015;McColl-Kennedy et al, 2017b), such active participation cannot necessarily guarantee a positive outcome (Echeverri and Sk al en, 2011;Watters et al, 2001;Zycinska et al, 2014). Their subjective evaluation of wellbeing (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy in the process of making a decision regarding breast reconstruction does not mediate between the outcome expectancies and intention, when the resources are poor. This may lead to the conclusion that low resources play a preventive role, guarding the patient against the feeling of dissatisfaction with breast reconstruction (see Zycinska, Gruszczynska, Choteborska, 2014). In view of the previously discussed conclusions and the contextual character of the examined variables, it is more justified to state that self-efficacy is a regulator in forming the intention and then in implementing it.…”
Section: Discussionmentioning
confidence: 99%
“…According to the known impact of sociodemographic variables and disease-related variables, it is the age and duration of the disease that may -to the highest degree -influence the decision to undergo breast reconstruction (e.g. Fallbjörk, Karrlson, Salander, Rasmussen, 2010;Girotto, Schreiber, Nahabedian, 2003;Lee, Hultman, Sepucha, 2010;Zycinska, Gruszczynska, Choteborska, 2014). Older women and those with a longer duration since diagnosis of the disease are less likely to opt for breast reconstruction.…”
Section: Aims Of the Studymentioning
confidence: 99%